Maintaining employment and improving health: A qualitative exploration of a job retention programme for employees with mental health conditions. Issue 1 (6th February 2017) - Woodall, James; Southby, Kris; Trigwell, Joanne; Lendzionowski, Vanessa; Rategh, Rosana
Abstract : Purpose: A proportion of the working age population in the UK experience mental health conditions, with this group often facing significant challenges to retain their employment. As part of a broader political commitment to health and well-being at work, the use of job retention services have become part of a suite of interventions designed to support both employers and employees. While rigorous assessment of job retention programmes are lacking, the purpose of this paper is to examine the success of, and distils learning from, a job retention service in England. Design/methodology/approach: A qualitative methodology was adopted for this research with semi-structured interviews considered an appropriate method to illuminate key issues. In total, 28 individuals were interviewed, including current and former service users, referrers, employers and job retention staff. Findings: Without the support of the job retention service, employees with mental health conditions were reported unlikely to have been maintained their employment status. Additional benefits were also reported, including improved mental health outcomes and impacts on individuals' personal life. Employers also reported positive benefits in engaging with the job retention service, including feeling better while being able to offer appropriate solutions that were mutually acceptable to the employee and the organisation. Originality/value: Job retention programmes are under researched and little is known about their effectiveness and the mechanisms that support individuals at work with mental health conditions. This study adds to the existing evidence and suggests that such interventions are promising in supporting employees and employers.